Cow size and milk level: results of a simulation program - R.R. Schalles; R.M. Bourdon (Kansas Agricultural Experiment Station Research Reports, 1986)
A simulation program was used to evaluate nine genotypes of cattle based on, cow size and milk production. Return per cow unit using current economics is given. The larger, heavy milking cows were more than twice as profitable on a ranch basis than the small, low milking cows.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Milk production; Cow size